Risk for Adult Obesity in Offspring of Pregnancies Affected by Hypertensive Diseases of Pregnancy [31H]. (May 2018) - Hammad, Ibrahim A.; Meeks, Huong; Fraser, Alison; Esplin, Sean M.; Smith, Ken; Varner, Michael
Abstract : INTRODUCTION: To determine if hypertensive disease of pregnancy (HDP) is associated with adult obesity in offspring. METHODS: A retrospective cohort study design was used to identify offspring of pregnancies complicated by HDP (gestational hypertension, preeclampsia, HELLP syndrome, eclampsia) born between 1947-1997 (now >20 years old) and with at least one adult BMI recorded in the Utah Population Database. These offspring (exposed) were matched by maternal age at birth, birth year, gender, and multiple gestation with offspring of women with no history of HDP (unexposed offspring). A second analysis was done matching the exposed offspring to their unexposed sibling in order to assess and control for the familial and environmental possible confounders. Adjusted relative risk (aRR) for obesity among exposed versus unexposed offspring as well as unexposed siblings were estimated using conditional logistic regression models. RESULTS: A total of 18, 009 exposed offspring were compared to 30, 761 unexposed offspring and 12, 579 exposed siblings to 26, 251 unexposed siblings. The relative risk of obesity was higher for exposed versus unexposed offspring, aRR=1.44 [95%CI 1.36-1.52]. Maternal obesity increased the relative risk to aRR=2.58 [95%CI 2.41-2.77], whereas higher maternal education decreased it to 0.87 [0.80-0.95]. For the sibling analysis, the risk for obesity was similar, aRR=1.05 [95%CI 0.98-1.11], aside from being a male sibling and first born aRR=1.31 [1.23-1.40] and aRR=1.18 [95%CI 1.09-1.27] respectively, no associated factors significantly increased the risk of obesity. CONCLUSION: HDP is independently associated with an increased the risk of obesity in adulthood. However this independent association was not demonstrated in the family, sibling environment.